Gestión de inventarios para la optimización de la rentabilidad y rendimiento en empresas PYMES, sector ferretero - Ponce Campodónico, Marola Lissette (2021)
The present essay entitled Inventory management for the optimization of profitability and performance in SMEs, hardware sector, was based on determining how inventory management affects small and medium-sized companies (SMEs) so that they reach optimal levels of profitability With respect to the indicators analyzed, the various financial elements related to the management of the Inventory and therefore to the profitability of the companies were studied, considering various theoretical contributions and research related to the area studied, as well as some legal documents..........